2021
DOI: 10.1002/jhbp.1052
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the degree of surgical difficulty anticipated for pancreatoduodenectomy: Preoperative and intraoperative factors

Abstract: Background Pancreatoduodenectomy (PD) is a technically complex procedure. Preoperative anticipation of the degree of difficulty could contribute to patient safety during trainee surgical education. Methods We prospectively administered a questionnaire to the chief surgeon after each PD performed between 2016 and 2018 at our institution (99 consecutive patients). The surgeon rated the difficulty of the procedure; we then analyzed this information against perioperative data. Results The difficulty of PD was rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Accurate preoperative assessment of surgical difficulty is crucial to the success of the surgery and patient safety. By predicting the difficulty of the surgical procedure before surgery, surgeons can better prepare for the surgery, optimize the surgical plan, and ensure patient safety during the operation ( 27 , 28 ). Su et al.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate preoperative assessment of surgical difficulty is crucial to the success of the surgery and patient safety. By predicting the difficulty of the surgical procedure before surgery, surgeons can better prepare for the surgery, optimize the surgical plan, and ensure patient safety during the operation ( 27 , 28 ). Su et al.…”
Section: Discussionmentioning
confidence: 99%
“…7 This undertaking is complicated by the fact that PD is not a uniform procedure due to anatomic variations in liver supply and branching pattern of superior mesenteric vessels, 8 the need to tailor the amount of retroperitoneal dissection based on disease and/or tumor type, 9 variability in digestive reconstruction techniques, 10 and different levels of technical difficulty. 11,12 Minimally invasive PD is associated with additional technical challenges that may sometimes result in major intraoperative adverse events requiring emergency conversion 13 and potentially increasing the risk of death. 14,15 The experience of the Pittsburgh group 16 and the LAELAPS-3 training program in the Netherlands 17 have shown that structured training programs permit safe implementation of RPD and reduce the learning curve for new adopters.…”
Section: Introductionmentioning
confidence: 99%
“…20 Also, in open PD, there is just 1 difficulty score, developed in 99 procedures without external validation. 12 We herein provide a new difficulty score for RPD, the PD-ROBOSCORE, developed within the International Consortium on Minimally Invasive Pancreatic Surgery (I-MIPS) (www.i-mips.com).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatoduodenectomy (PD) is a demanding procedure that, among gastrointestinal surgeries, requires a high level of skill and appropriate perioperative management 1–5 . Pancreatic cancer accounts for the majority of diseases requiring pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatoduodenectomy (PD) is a demanding procedure that, among gastrointestinal surgeries, requires a high level of skill and appropriate perioperative management. 1 , 2 , 3 , 4 , 5 Pancreatic cancer accounts for the majority of diseases requiring pancreatectomy. In recent years, advances in multidisciplinary treatment for pancreatic cancer have led to an increase in the 5‐year survival rate of pancreatic cancer patients and an increase in the number of patients who survive for a long period.…”
Section: Introductionmentioning
confidence: 99%